2017
DOI: 10.1099/mic.0.000496
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial communities in the small intestine respond differently to those in the caecum and colon in mice fed low- and high-fat diets

Abstract: Bacterial communities in the mouse caecum and faeces are known to be altered by changes in dietary fat. The microbiota of the mouse small intestine, by contrast, has not been extensively profiled and it is unclear whether small intestinal bacterial communities shift with dietary fat levels. We compared the microbiota in the small intestine, caecum and colon in mice fed a low-fat (LF) or high-fat (HF) diet using 16S rRNA gene sequencing. The relative abundance of major phyla in the small intestine, Bacteriodete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 43 publications
(49 reference statements)
6
35
0
Order By: Relevance
“…Due to the strong correlative relationship between the QTL, we tested whether there was a direct interaction between bile acids and Turicibacter . Turicibacter inhabits the small intestine where BAs are secreted upon consumption of a meal (73,74). We screened the human isolate Turicibacter sanguinis for deconjugation and transformation activity in vitro by HPLC/MS-MS. We found that T. sanguinis deconjugated ∼96-100% of taurocholic acid and glycochenodeoxycholic acid (Fig 5A) within 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the strong correlative relationship between the QTL, we tested whether there was a direct interaction between bile acids and Turicibacter . Turicibacter inhabits the small intestine where BAs are secreted upon consumption of a meal (73,74). We screened the human isolate Turicibacter sanguinis for deconjugation and transformation activity in vitro by HPLC/MS-MS. We found that T. sanguinis deconjugated ∼96-100% of taurocholic acid and glycochenodeoxycholic acid (Fig 5A) within 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…These microorganisms may promote intestinal homeostasis and may protect against inflammatory diseases [54][55][56][57]. Vitamin B12 is absorbed in the small intestines [58][59][60] while the majority of microbiota reside in the colon [58], although, the small intestine is not sterile and does contain a robust microbiota that influences the absorption of vitamins [61][62][63]. Specific bacteria produce vitamin B12 [64], and the children infected with G. duodenalis with DNA levels above 1 fg/µl may be unable to synthesize the required amounts of vitamin B12 for nutritional benefit.…”
Section: Changes In Vitamin B12 Due To Parasite Infectionsmentioning
confidence: 99%
“…Moreover, the microvasculature of the SB comprises a rich network of capillaries that lie in the submucosal layer of the SB, allowing for rapid absorption of nutrients such as amino acids, fatty acids, and monosaccharides (160) into the bloodstream and distribution to the other organs (157)(158)(159). The SB contains a relatively lesser number of bacteria, with the major phyla being Bacteriodetes, Firmicutes, and Proteobacteria and anaerobes such as Lactobacillus species being the most predominant genera (161). The colon, on the other hand, averages at about 1.5-2 m in humans and consists of 6 sections, beginning with the cecum and followed by the ascending colon, transverse colon, descending colon, the S-shaped sigmoid colon, and, lastly, the rectum.…”
Section: Function Of the Gutmentioning
confidence: 99%